Statistical process control - Baritugo, Jean-Paul B.; Putong, Arnold M. (1995)
Statistical Process Control or SPC is used to document, evaluate and improve the level of quality of a process or a product with the use of statistical tools and techniques. The use of SPC is most extensive in a manufacturing setting where the quality issue is significant. In a manufacturing setting, no two things are made exactly alike. There are always variations that would make a product different. Variations are present because of the interactions of the following variables: Men, Machine, Materials and Environment. As long as these variations fluctuate in a normal manner, the variations in a product will be due to random chances. However, when these variations occur in a unnatural manner, the variations will be due to assignable caesuras, i.e. significant effects are being made by one or a combination of the above variables. The Statistical Process Control Software is used to indicate if these variations are natural or not. It is a graphical method of presenting the quality level of a particular product or process. It automates the process of setting up and evaluating the quality of a particular product/process characteristic with the use of statistical concepts. The ultimate objective of the software is to provide a Quality Improvement Tool for local manufacturers. This is a Windows based application developed using the 4GL Visual Basic platform. The product has the following features: 1. Variable Control Charts: X-R and X-S charts. Used to monitor the variability of characteristics that are measurable. 2. Attribute Control Charts: p/np and the c charts. Used to monitor the variability of characteristics that are not measurable (color, surface finish) or measurable but evaluation is reduced such that there are only two outcomes. 3. Capability Analysis: Gives the capability ration of a process in reference to the product specification limits. 4. Histogram Generator: Generates frequency distribution of values inputted. 5. Pareto Chart Analysis: Generates frequency distribution of values inputted. 5. Pareto Chart Analysis: Generates Pareto Chart that determines largest contributor to some quality problems. The finished product is being tested in real manufacturing setting in a factory that manufactures chocolates, marshmallows, and the like. Initial problem that the manufacturer pointed out were moisture content, total soluble solid in product, length of cuttings, weight of packages, etc. The results of this testings are contained in a case study.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Process control -- Statistical methods -- Computer programs; Quality control -- Statistical methods -- Computer programs; Statistical process control; Quality improvement tool